(untitled) (Research, Society and Development, 2017)
This paper aims to present two activities elaborated with the Matlab software on the teaching of Mathematical concepts of Solid of Revolution in the x and y axes, used as pedagogical support tool with students of an Engineering course, complementing the expositive classes on the same subject . The methodology used is of the academic type, seeking to extend the knowledge in the discipline Differential and Integral Calculus regarding the teaching-learning process. Based on the results obtained, we can prove the importance of the use of such a tool in the teaching-learning process because the classroom became a differentiated moment, through the interaction and motivation of the student, who actively participates in his or her learning with better or better use of the lecture.